EFFECT OF FERMENTATION DURATION ON THE ELECTRICAL PROPERTIES OF KETAPANG AND TAMARIND EXTRACTS - Afrida, Juniar; Mauliza, Ririn (EduFisika: Jurnal Pendidikan Fisika, 2024)
Ketapang fruit (Terminalia catappa L.) and tamarind fruit (Tamarindus indica L.) contain electrolytes that have the potential to serve as alternative energy sources for bio-batteries. This study aims to examine the effect of fermentation duration of extracts from both fruits on pH, electrical voltage, electrical current, and electrical power. This is an experimental study. The fruit samples were fermented for 10 days with varying concentrations of 50, 100, 150, 200, and 250 ppm for each solution. Measurements were carried out using a digital pH meter and a multimeter to determine the electrochemical characteristics. The results showed that the pH of the solution tended to increase during fermentation, with the lowest pH recorded on day 0 in the tamarind solution (250 ppm, pH 6.4) and the highest on day 10 in the ketapang solution (50 ppm, pH 8.1). The electrical voltage of the ketapang solution at all concentrations showed a fluctuating trend. The electrical current consistently showed negative results (-0.010 to -0.020 mA), indicating that the direction of charge flow was opposite to conventional outputs. The electrical power was directly proportional to the voltage and current but showed instability in the ketapang solution. The alkalization process during fermentation contributed to changes in the electrochemical properties of the solution. The increase in pH influenced ion conductivity and electrochemical mechanisms, such as the movement of hydroxide ions (OH-minus). This study indicates that ketapang and tamarind fruits can be utilized as alternative energy sources for bio-battery.